دور جدارات المحاسب الاداري في تحسين وظيفة المحاسبة الادارية (دراسةاستطلاعية لعينة من الاكاديميين و المهنيين العاملين في محافظة السليمانية)البحث - نجم, أ.م. د.بصيرة مجيد; فرج, دانا جلال (Sulaimani Journal for Humanities, 2023)
The study aims to demonstrate the importance of the role of the competencies of the management accountant in raising the scientific and practical efficiency of the management accountant, which contributes to improving the function of management accounting by applying to a sample of academics and professionals working in Sulaymaniyah Governorate and in order to achieve the objective of the study, the researchers tested the hypotheses of the study by relying on the questionnaire form as a data collection tool necessary for the preparation of this study, where the form was distributed to 135 individuals from academics and professionals and 100 forms were valid for analysis, i.e. 74% of the total two samples by (88% and 87% respectively. The study reached several conclusions, namely: The results of the field side showed that there is great importance of management accounting in improving the function of management accounting, as the arithmetic mean of both samples reached (4.08, 4.03) respectively. The relative importance reached (81.59% and 80.64%) respectively. It was clear from the results of the field side that the existence of the competencies of the management accountant contributes to improving the function of management accounting.
Keywords: Management Accounting Competencies; Management Accounting; Improving the Function of Management Accounting